United we stand : the role of spirituality in engaging and healing communities - Davis, Dannielle Joy, 1974- (Emerald Publishing Limited : Information Age Publishing, inc., 2020)
"Segments of society are drawing upon their faith and spirituality to develop strategies to mend social relationships and fragmented communities. The Contemporary Perspectives on Spirituality in Education book series will feature volumes geared towards understanding and exploring the role of spirituality in addressing challenge, conflict, and marginalization, particularly within education in the U.S. and internationally"-- Provided by publisher.
Keywords: Education -- Religious aspects.; Church and education.; Community organization -- Moral and ethical aspects.; Spirituality.; Education -- Schools -- Types -- Religious.; Faith (religious) schools.; elektronické knihy; electronic books